Liver Disease in Adolescents: A Cohort Study of High-Risk Individuals. - Van der Poorten, D.; Kenny, D.; Butler, Tony; George, J. (American Association for the Study of Liver Diseases., 2007)
Little is known about the health and behavior of adolescent offenders as they relate to abnormalities of liver biochemistry and hepatitis C virus (HCV) infection. A large study of male juvenile offenders was undertaken that allowed a re-evaluation of the normal limits of alanine aminotransferase (ALT), associations with elevated ALT, and HCV antibody positivity. Young offenders (age 12-19 years) serving community orders participated in a wideranging health survey and laboratory assessment between October 2003 and December 2005. Normal ranges for liver biochemistry were calculated from the 95th percentile of males at the lowest risk for liver disease. The final sample comprised 682 males, of whom 439 (64%) gave blood. The calculated upper limit of normal for ALT was 28 IU/L. Seventeen percent of adolescents had an elevated ALT. Strong associations with elevated ALT included HCV antibody positivity [odds ratio (OR) 14.6], overweight and obesity (OR 6.9), and elevated total cholesterol (OR 3.6). More than 90% of adolescents with elevated ALT levels had 1 or more features of the metabolic syndrome. HCV antibody was positive in approximately 3% of the cohort, with the most significant risk factor being injecting drug use (OR 7.8; P < 0.01). The new infection rate was 3.7% per year. Conclusion: New upper limits for ALT provide greater sensitivity for the early diagnosis of liver disease in adolescents. High rates of HCV infection and obesity-related liver disease exist in this group, and targeted interventions are needed to reduce future health-related morbidity. (HEPATOLOGY 2007;46: 1750-1758.)